The Use of Constructivism Approach in Learning to Find Intrinsic Elements of Prophetic Short Stories through Google Form - Zohomi, Norhidayah Azni Mohamed; Kusaini, Ezwafahmey Ahmad (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to explore: 1) the use of a constructivist approach in learning to find intrinsic elements of prophetic short stories through Google Form based on student responses; 2) learning outcomes in finding intrinsic elements of prophetic short stories through Google Forms The study was conducted at Sekolah Menengah Kebangsaan Shahbandaraya, Klang, Selangor, Malaysia, at the beginning of the odd semester of the 2025 academic year. The population of this study consisted of 5th-grade students who participated in learning to identify intrinsic elements of prophetic short stories using a constructivist approach through Google Form media. There were 32 students. This study employed a total sample, utilizing all population members as sample members. The first instrument of this study was the implementation plan for learning to identify intrinsic elements in prophetic short stories using a constructivist approach administered through Google Form. The second instrument was a questionnaire that assessed student responses to learning. The third instrument was a test to find intrinsic elements of prophetic short stories. All instruments were compiled using objective and systematic procedures. Student response-based learning data were analyzed using frequency and percentage. Learning outcome data were analyzed using descriptive statistical procedures, namely mean and percentage. Research results: 1) the learning procedure to find intrinsic elements of prophetic short stories using a constructivist approach through Google Form involves learning activities that are enjoyed by students; 2) the learning outcomes to find intrinsic elements of prophetic short stories using a constructivist approach through Google Form are in the high category.